Biodiversity dynamics of terrestrial gastropods in the tropical montane rainforests of Nuwara Eliya, Sri Lanka - Thilakarathne, Dinelka D.; Ranawana, Kithsiri B; Kumburegama, Shalika (Archives of Biological Sciences, 2024)
Paper description: Sri Lanka is home to 253 terrestrial gastropod species with more than 80% endemic species. Research exploring their diversity, distribution, and influencing variables is limited. This study sampled gastropods in tropical montane rainforests, utilizing 1 m2 plots across 60 randomly selected sites. Of the species recorded, 79% were native, 17% were exotic. Exotic species exhibit broader environmental tolerance compared to natives, allowing them to invade forests. Native species confined to deep canopy forests are vulnerable to habitat changes. Exotic species that thrive under altered conditions highlight the importance of conserving these forests. Abstract: Sri Lanka is home to 253 terrestrial gastropod species, most of which are endemic. However, limited research has explored the diversity, distribution, and influencing variables of these gastropods. This study sampled gastropods in tropical montane rainforests by establishing 10-50 1-m2 sampling plots across 60 randomly selected sites. Among the 46 recorded species, 79% were native, and 17% were exotic. Species representative of the five endemic genera to the island and two endemic semi-slug species were recorded from these forests. Native gastropod species were primarily found in forest interiors, while exotic species inhabited forest buffer regions. The distribution of most native species is influenced by elevation, air temperature, relative humidity, rainfall, and soil pH, while elevation and rainfall play a significant role in the distribution of most exotics. Exotics display broader environmental tolerance compared to natives, enabling exotics to invade the forests. The restricted habitat of many native species within deep canopy forests makes them highly vulnerable to habitat change, whereas exotics thrive under altered conditions.